UNDERSTANDING GENDER JUSTICE PERSPECTIVE OF AMIN WADUD MUHSIN : MENGURAI KEADILAN GENDER PERSPEKTIF AMINA WADUD MUHSIN - Ari Susetiyo; Zetty Azizatun Ni’mah (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
Understanding or interpretation of a text, including the holy book of the Qur'an, is stronglyinfluenced by the perspective of the commentator, cultural background, and prejudices behind it.In this way the text becomes alive and rich in meaning. The meaning of the text becomes dynamicand always contextual, along with the acceleration of the development of human culture andcivilization. Amina Wadud carries out her creativity and innovation in interpreting the Qur'an.Because so far there is no truly objective method of interpretation. Each interpretation tends toreflect subjective choices. The reconstruction of Amina Wadud's interpretation methodology ischaracterized by Deconstructive-reconstructive, Argumentative-theological and Hermeneuticphilosophical, each verse to be interpreted must be analyzed in various aspects. n the study ofleadership, Amina's critique of the male Mufassir that men were created by Allah to be superior towomen (in terms of physical and mental strength) ignores the sociological contextual aspect whichis contrary to the spirit of justice and humanity in Islamic teachings.